Determinacion de hongos internos, presentes en la semilla de poroto - Nitsche M, J.=700 1 Cafati K, C.
(Es, En)
Ilus., 12 ref.
Keywords: HONGOS ENTOMOPATOGENOS; SEMILAS; FRIJOL (PHASEOLUS); CHILE; POROTO; AGRICULTURA TECNICA